Nanotechnology and Carbon Nanotubes; A Review of Potential in Drug Delivery - Kamalha, Edwin; Shi, Xiangyang; Mwasiagi, Josphat I.; Zeng, Yongchun (Macromolecular Research, 2012)
The need for affordable health care costs and the quest for better modes of treatment have increased research in novel drug delivery techniques. Efficient drug delivery systems (DDS) are judged on their ability to perform controlled and targeted drug delivery. Several nanomaterials such as carbon nanotubes (CNTs) are widely being investigated for biomedical use due to their unique properties, as well as several functional groups and incorporated targeting molecules. This review looked at nanotechnology as an emerging field in drug delivery. Several studies and findings with regards to the current functionalization of CNTs for drug delivery were explored. The conclusion reviewed the key notes.
Keywords: Drug delivery systems (DDS); Carbon nanotubes (CNTs); Single-walled nanotubes (SWNTs); Multi-walled nanotubes (MWNTs); Functionalization